Influence of graft anastomosis and graft morphology on long-term patency of the saphenous vein after aortocoronary bypass - Okantey, Okaikor; Jonszta, Tomas; Sieja, Jiri; Kende, Miriam; Brat, Radim; Pavliska, Lubomir (Biomedical papers, 2024)
Objective. Several factors are involved in the preservation of graft function after surgical myocardial revascularization. This follow-up study aimed to evaluate the effects of vein graft anastomosis and graft morphology on long-term graft patency a minimum of 10 years after aortocoronary bypass grafting.Setting and Cohorts. This was a sub-analysis of a study that enrolled patients after isolated bypass surgery at the University Hospital Ostrava in order to evaluate the long-term graft patency of the saphenous vein after endoscopic harvest, a minimum of 10 years after aortocoronary bypass grafting. Methods. Fifty angiograms, with a total of 90 grafts, after isolated myocardial revascularization were visualized using coronary computed tomography angiography, with 50% luminal stenosis or greater considered significant. Results. The overall graft patency rate was 72.3%. The differences in occlusion rates between sequential and individual grafts were not statistically significant (P=0.156). All y-grafts were totally occluded. Graft and target artery diameters had a statistically significant influence on patency (P=1.000 and 0.381, respectively). Longer graft length and higher calcium scores were associated with statistically significant graft occlusion (P=0.033 and 0.005, respectively). Conclusion. Sequential grafts can be constructed safely, especially when the goal is complete myocardial revascularization.
Keywords: sequential graft; graft patency; calcium score; graft morphology; target quality; graft length